Traces of the Influence of Attic Tragedy on the Poetry of Moschus - Kudulytė-Kairienė, Audronė (Literatūra, 2015)
The article deals with the role of Classical Greek tragedies in the Hellenistic period and their influence on the poetry of that period. The importance of Hellenistic drama was much less than that of Classical drama. Old tragedies were performed, studied and edited during all the Hellenistic period. The poets of that period are known as poetae docti, they had got a good knowledge of the poetry of the past centuries. One of the Hellenistic poets Moschus lived and wrote during the second century B. C. He was grammarian, a pupil of Alexandrian philologist Aristarchus. Like many others Hellenistic poets, Moschus wrote bucolic poetry, short epic poems and epigrams. His language is very closely Homeric. The analysis of the poets’ short epic poems Megara and especially his masterpiece Europe reveals that Moschus was derivative author and used many litterary sources, not only Homer and Hellenistic poetry (Theocritus, Apollonius Rhodius), but an Attic tragedy as well. The traces of influence of Aeschylus, Sophocles and Euripides on Moschus’ poetry are analysed (Aesch. Pers. 181–187; Soph. frg. 881; Eur. frg. 820 etc.).